Efforts to Increase Digital Literacy in Class XII Students at Budi Agung Private Vocational School Medan - Nasib; Harianto, Adi; Juliansyah, Roni; Novirsari, Emma; Honkley, Tony; Martin; Hervina Sihombing, Ester; Hastuty HS, Widy; Amelia, Ratih; Tambunan, Debora (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2024)
Digital literacy is the ability to use information and communication technology (ICT) effectively and critically. Digital literacy can involve the ability to find, evaluate, use and create information through various digital platforms. On this occasion, the focus was on increasing digital literacy for students in class XII of Budi Agung Private Vocational School, Medan. In this community service activity, face-to-face seminars and basic training are carried out for all students. Digital literacy can certainly provide benefits for students. The benefits that can be felt with digital literacy are that students can access various sources of information to support learning, help with assignments, teach students to evaluate the reliability and validity of online information sources which will also be useful as preparation for the world of work.